Standardizing assessment practices of undergraduate medical competencies across medical schools: challenges, opportunities and lessons learned from a consortium of medical schools in Uganda - Gonzaga Mubuuke, Aloysius; Mwesigwa, Catherine; Maling, Samuel; Rukundo, Godfrey; Kagawa, Mike; Lagoro Kitara, David; Kiguli, Sarah (Pan African Medical Journal, 2014)
Health professions education is gradually moving away from the more traditional approaches to new innovative ways of training aimed at producing professionals with the necessary competencies to address the community health needs. In response to these emerging trends, Medical Education for Equitable Services to All Ugandans (MESAU), a consortium of Ugandan medical schools developed key competencies desirable of graduates and successfully implemented Competency Based Education (CBE) for undergraduate medical students. Objectives: to examine the current situation and establish whether assessment methods of the competencies are standardized across MESAU schools as well as establish the challenges, opportunities and lessons learned from the MESAU consortium. Methods: It was a cross-sectional descriptive study involving faculty of the medical schools in Uganda. Data was collected using focus group discussions and document reviews. Findings were presented in form of themes. Results: Although the MESAU schools have implemented the developed competencies within their curricular, the assessment methods are still not standardized with each institution having its own assessment procedures. Lack of knowledge and skills regarding assessment of the competencies was evident amongst the faculty. The fear for change amongst lecturers was also noted as a major challenge. However, the institutional collaboration created while developing competencies was identified as key strength. Conclusion: Findings demonstrated that despite having common competencies, there is no standardized assessment blue print applicable to all MESAU schools. Continued collaboration and faculty development in assessment is strongly recommended.
Keywords: MESAU; Competencies; Assessment